(untitled) (Revista de História da UEG (REVHIST), 2025)
The article analyzes the social uses from the Square of sunflowers, in the city of Palmas-TO from 2006 to 2020. The research is based on oral sources through interviews with the visitors of this urban space. The study highlights the sociabilities developed in the area, mainly through physical activities, and discusses the mechanisms of control and surveillance of the body, as well as the gender relations established there. Furthermore, it presents theoretical reflections based on the categories of history and city, history and memory, gender relations, and social control, in dialogue with various authors. The results indicate the different uses and representations of Square of sunflowers, highlight the forms of social control based on gender, and emphasize the construction of the idea of place attributed to this space in the city of Palmas. Keywords: History and City. History and Memory. Urban Sociabilities. Gender Relations and Social Control.